PENILAIAN RISIKO KERJA TERHADAP KECELAKAAN KERJA DI PT. TEGUH KARSA WANA LESTARI KECAMATAN BUNGARAYA KABUPATEN SIAK - Riski Novera Yenita (STIKes Al-Insyirah Pekanbaru, 2018)
Accident of Activity represent an occurence which do not be anticipated and do not be wanted by company hence company have to apply method of HIRARC represent to with refer to process of mengidentivikasi danger able to happened in routine activity and also non routine in company, this method isused to lessen accident of activity so that more is recognizing of potency things able to generate accident of this kerja.Penelitian aim to to know relation Accident Of Activity To Assessment of Risk Work in part of production in PT. Unshakeable of Everlasting Karsa Wana. this Method Research is to represent study evaluate by using quantitative approach. With sampel counted 33 worker people part of production in PT. Unshakeable of Everlasting Karsa Wana. Analysis Data conducted by using test of chi square with computer at storey;level of signifikan p= 0,004 <α = 0.005 result of which in obtaining to show there is relation which is signifikan between accident of activity to assessment of activity risk. Conclusion of accident of activity very is having an effect on of strength to Assessment of Risk work in part of production of PT. Unshakeable of Everlasting Karsa Wana.